Cognitive Emotion Regulation Strategies and Mindfulness: Key Determinants of Wellbeing Among Young Adults - Ryan Macey Wise; Esmahan Banu Yildiz (Journal of Psychological Perspective, 2026)
This article addressed the predictor role of mindfulness and cognitive emotion regulation strategies on wellbeing. I expected that individuals who score higher on mindfulness use, more adaptive emotion regulation strategies, and less non-adaptive emotion regulation strategies would score higher on wellbeing. The present article used a correlational design to investigate the associations between cognitive emotion regulation strategies, wellbeing, and mindfulness in young adult participants. One hundred seventy-five university students were recruited for this study. Correlation analysis showed that mindfulness and wellbeing were significantly and positively correlated. Multiple regression analysis showed that emotion regulation strategies of Self-blame and Planning were significant predictors of wellbeing. University students' wellbeing might be enhanced when they use planning strategies and dampened when they use self-blame to cope with stressful events.